Domestic Water Distribution Planning from Springs in Jatimulyo Village, Girimulyo District, Kulon Progo - Adam Pamudji Rahardjo; Budi Kamulyan; Radianta Triatmaja; Anzhari Syahmi; Nurul Purnama Sari; Sunjoto Sunjoto; Dyah Dhani M.; Raelly Harza W. (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
During the dry season, most of the springs in Jatimulyo Village deliver less water. This condition causes difficulties for people in the area. Only two springs supply sufficient water for distribution. Therefore, it is necessary to optimize the water distribution from the two springs, Mudal and Sumitro. This study aims to provide an alternative technical plan for the distribution of domestic water and to provide recommendations in the distribution and regulation of the use of water from the Mudal and Sumitro springs to the local authority and community in Jatimulyo Village. The distribution system relies on gravity so that it does not require any pump. This study has conducted using the hydraulic equation for water flow through a pipe to analyze the design water discharge required for each reservoir. For water distribution planning, counting the number of houses that will be served was conducted using Google Earth imagery. The results of this study indicate that from the Mudal spring, water distribution pipelines can cover 282 houses, with a total required water discharge of 1,632 liters/second. For the Sumitro spring, the first alternative scheme can serve 161 houses and requires 0.932 liters/second water discharge. As for the second alternative, it is estimated to be able to serve 138 houses with a total required water discharge of 0.799 liters/second. It is necessary to measure all spring discharge every month. It will help determining the fluctuation of the discharge of each spring.